2021
DOI: 10.1093/heapol/czab002
|View full text |Cite
|
Sign up to set email alerts
|

Looking into the performance-based financing black box: evidence from an impact evaluation in the health sector in Cameroon

Abstract: Performance-based financing (PBF) is a complex health systems intervention aimed at improving the coverage and quality of care. Several studies have shown a positive impact of PBF on health service coverage, often coupled with improvements in quality, but relatively little is known about the mechanisms driving those results. This article presents results of a randomized impact evaluation in Cameroon designed to isolate the role of specific components of the PBF approach with four study groups: (i) PBF with exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 21 publications
4
20
0
Order By: Relevance
“…In Zambia, P4P was found to have no significant effect on the availability of inputs (facility infrastructure, drugs, or equipment), process quality of care (antenatal and child health care exit interviews), and client satisfaction [ 43 ]. In Cameroon, there was no evidence of an effect of P4P on process quality of care measured using direct observation of antenatal and childcare consultations [ 44 ]. Finally, in Benin, P4P had a significant effect on various aspects of clinical care, including a 5.5 percentage point, 2.7 percentage point, and 8.8 percentage point increase in checklists for history taking, physical examinations and advice during antenatal care consultations [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Zambia, P4P was found to have no significant effect on the availability of inputs (facility infrastructure, drugs, or equipment), process quality of care (antenatal and child health care exit interviews), and client satisfaction [ 43 ]. In Cameroon, there was no evidence of an effect of P4P on process quality of care measured using direct observation of antenatal and childcare consultations [ 44 ]. Finally, in Benin, P4P had a significant effect on various aspects of clinical care, including a 5.5 percentage point, 2.7 percentage point, and 8.8 percentage point increase in checklists for history taking, physical examinations and advice during antenatal care consultations [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…the availability of inputs (facility infrastructure, drugs, or equipment), process quality of care (antenatal and child health care exit interviews), and client satisfaction [43]. In Cameroon, there was no evidence of an effect of P4P on process quality of care measured using direct observation of antenatal and childcare consultations [44]. Finally, in Benin, P4P had a significant effect on various aspects of clinical care, including a 5.5 percentage point, 2.7 percentage point, and 8.8 percentage point increase in checklists for history taking, physical examinations and advice during antenatal care consultations [45].…”
Section: Plos Medicinementioning
confidence: 99%
“…22 Several evaluations of PBF programmes have found that a comparison group that maintains resource neutrality and includes decentralisation can lead to equivalent gains in coverage although with differential impacts on quality of care. [23][24][25] While PBF interventions provide an unconditional core budget and additional financial incentives conditional on performance, DFF interventions only provide additional unconditional financing. Often the financing is accompanied by autonomy, community engagement and supportive supervision.…”
Section: Do Financial Incentives Work?mentioning
confidence: 99%